The emergence of algebraic thinking: students’ strategies concerning the notion of mathematical equivalence (Edma 0-6: Educación Matemática en la Infancia, 2019)
In this article, we present the results of a collaborative research conducted in Ontario. The objective of the study was to characterize preschool students’ algebraic thinking strategies concerning the notion of mathematical equivalence. To do so, we proposed two tasks to 36 students from three different classes and analyzed their strategies. Our results highlight 14 strategies used by students to work with the concept of equivalence; within these, three facilitated reasoning associated to algebraic thinking. Our research demonstrates that preschool children can reason on the notion of equivalence in a relational manner well before algebra is formally introduced.
Keywords: Algebraic thinking; Mathematical equivalence; Strategies; Students; Preschool